Pengaruh Pembelajaran Menulis Teks Eksplanasi Berbasis Project Based Learning - M Apri Yoza Aditya Surya; Hary Soedarto Harjono; Ade Bayu Saputra (Jurnal Ilmiah Dikdaya, 2026)
This study aims to determine the effect of Project Based Learning (PjBL) on students’ ability to write explanatory texts. The research employed a quantitative approach using a pretest–posttest control group experimental design. The subjects were tenth-grade vocational high school students divided into experimental and control groups. Data were collected through explanatory text writing tests administered before and after the treatment. Data analysis used N-Gain and Independent Sample t-Test. The results indicate a significant difference in the improvement of students’ explanatory text writing skills between the experimental and control groups. Therefore, Project Based Learning has a significant effect on improving students’ explanatory text writing skills.